2021
DOI: 10.3390/agriculture11111069
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ultrasound and Curing Agent during Osmotic Dehydration to Improve the Quality Properties of Freeze-Dried Yellow Peach (Amygdalus persica) Slices

Abstract: This study aimed to improve the quality of freeze-dried yellow peaches (Amygdalus persica). Yellow peaches were pretreated with osmotic dehydration for 15 min prior to vacuum-freeze drying and supplemented with different ultrasonic power levels (180 W, 240 W, 300 W) and a curing agent (calcium lactobionate, CaLa) to investigate the effects on the quality of freeze-dried yellow peach slices. After vacuum freeze-drying the yellow peach slices for 48 h, their moisture, color, texture, microstructure, total phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…The average rehydration ratio of apple slices decreased from 237.7 to 177.5%, by increasing osmotic solution concentration from 30 to 50%. The use of ultrasound and curing agents during OD for enhancing the quality characteristics of freeze-dried yellow peach slices was examined by Chu et al 24 . The authors reported that with increasing ultrasound treatment time, the drying time and shrinkage of the product would reduce.…”
Section: Resultsmentioning
confidence: 99%
“…The average rehydration ratio of apple slices decreased from 237.7 to 177.5%, by increasing osmotic solution concentration from 30 to 50%. The use of ultrasound and curing agents during OD for enhancing the quality characteristics of freeze-dried yellow peach slices was examined by Chu et al 24 . The authors reported that with increasing ultrasound treatment time, the drying time and shrinkage of the product would reduce.…”
Section: Resultsmentioning
confidence: 99%
“…The use of ultrasonic waves and curing agents during osmosis dehydration to enhance the quality attributes of freeze-dried yellow peach pieces was studied by Chu et al [22]. The authors indicated that product drying time and shrinkage decreased as the sonication time increased.…”
Section: Peachesmentioning
confidence: 99%
“…Recently, various combination techniques have been examined to improve dehydration speed and save energy when freeze-drying fruits and vegetables. These include the combination of the FD technique with other techniques, as assisted or pretreatment, such as ultrasound [20][21][22][23][24], microwaves [18,[25][26][27], vacuum [28], pulse-spouted microwave vacuum [26], CO 2 laser perforation [29][30][31], pulsed electric field (PEF) [32][33][34][35], and infrared radiation [1,[36][37][38]. As a result, these techniques reduce the processing time and cost, and improve the quality of the final products.…”
Section: Introductionmentioning
confidence: 99%
“…In the face of the advantages and disadvantages of each main ultrasound technology, most applications rely on ultrasound pre-treatments in ultrasonic baths followed by traditional drying techniques, such as oven [20] , [107] , forced convective [27] , [28] , [37] , [143] , [144] , fluidized bed [145] , [146] , microwave [147] , [148] , [149] , infrared [92] , [93] , [102] , [118] , vacuum-assisted [150] , [151] , and freeze-drying [152] , [153] , [154] .…”
Section: Goal #9 – “Industry Innovation and Infrastructure”mentioning
confidence: 99%